PEMBERDAYAAN KELOMPOK PKK MELALUI GERAKAN "CEGAH DBD" BERBASIS INOVASI KEARIFAN LOKAL - Desy Fadilah Adina Putri; Fitri Setianingsih; Anak Agung Ngurah Ketut Riyadi; Nurlaila Agustikawati (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The increase in dengue fever cases is influenced by the rainy season, which creates an ideal environment for the development of the Aedes aegypti mosquito. Furthermore, dengue fever can be caused by several behaviors that arise as a result of a lack of health education related to dengue fever, and a lack of community skills in utilizing natural ingredients as a substitute for chemical mosquito repellents. Therefore, it is necessary to empower mothers who are the frontline of family health to increase their knowledge and skills to protect their families from dengue fever. This activity aims to increase knowledge, skills, and motivation in preventing and handling the emergence of dengue fever. The method of this activity is education, training, and direct practice with target partners, namely the Family Welfare Movement (PKK) group. The results of this activity obtained an increase in knowledge from 12.5% ​​with good knowledge to 90% with good knowledge, from 20% skilled to 85% skilled in making serute mosquito repellent. Therefore, it can be concluded that this partner empowerment activity is able to increase the knowledge and skills of the PKK group. Therefore, it is recommended that the PKK group actively encourage residents and cadres to utilize household kitchen ingredients to make natural mosquito repellents and continue to maintain the cleanliness of the house and environment to avoid dengue fever.